2000
DOI: 10.1074/jbc.c000629200
|View full text |Cite
|
Sign up to set email alerts
|

CLIF, a Novel Cycle-like Factor, Regulates the Circadian Oscillation of Plasminogen Activator Inhibitor-1 Gene Expression

Abstract: The onset of myocardial infarction occurs frequently in the early morning, and it may partly result from circadian variation of fibrinolytic activity. Plasminogen activator inhibitor-1 activity shows a circadian oscillation and may account for the morning onset of myocardial infarction. However, the molecular mechanisms regulating this circadian oscillation remain unknown. Recent evidence indicates that basic helix-loop-helix (bHLH)/PAS domain transcription factors play a crucial role in controlling the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
162
4
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(179 citation statements)
references
References 32 publications
9
162
4
1
Order By: Relevance
“…2A). However, rhythmic PAI-1 mRNA expression was damped in the hearts of control Clock mutant mice (F [3,16] Plasma levels of total PAI-1 antigen were obviously increased by STZ in both WT and Clock mutant mice (F[1,32] = 45.1, P < 0.01 and F[1,33] = 23.8, P < 0.01, respectively) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). However, rhythmic PAI-1 mRNA expression was damped in the hearts of control Clock mutant mice (F [3,16] Plasma levels of total PAI-1 antigen were obviously increased by STZ in both WT and Clock mutant mice (F[1,32] = 45.1, P < 0.01 and F[1,33] = 23.8, P < 0.01, respectively) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Maemura et al [3] described the circadian expression of PAI-1 mRNA in the heart and kidneys of mice, and suggested that the circadian oscillation of PAI-1 gene expression plays an important role in the circadian fluctuation of blood fibrinolytic activity. Assays in vitro have shown that CLOCK:BMAL2 (CLIF) and CLOCK:-BMAL1 heterodimers up-regulate human PAI-1 gene expression via E-box (CACGTG) elements located at bp À677 to À672 and at bp À562 to À557 [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in blood glucose, insulin and triglyceride levels produces Pai-1 mRNA expression in the liver [30], and insulin and triglycerides synergistically induce Pai-1 biosynthesis in hepatocytes [30]. Previously published data suggest that the CLOCK:BMAL2 (or BMAL1) heterodimer may be responsible for regulating mPai-1 circadian expression [6]. All of these factors together may cause a constant high level of mPai-1 gene expression in the liver of db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study shows that mammalian peripheral tissues contain an oscillator that couples to a central oscillator under normal conditions [3], and the clock genes in these peripheral tissues show clear circadian rhythms [4]. Plasminogen activator inhibitor type 1 (PAI-1), a primary regulator of the fibrinolytic cascade, has two functional E-box motifs in the promoter [5], and its gene expression is regulated by the circadian clock [6].…”
Section: Introductionmentioning
confidence: 99%